Assessing IT Proficiency in Educational Workplaces of Thailand’s Southern Border Provinces: An Exploratory Sequential Mixed Methods Approach - Kaewjomnong, Aniwat; Makkongka, Wasana (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
The rapid changes in educational institutions require the adoption of more information technology in the organization. This may affect the unskilled personnel who may not be able to use it in their jobs effectively in order to create modern educational institutions. The objective of this research was to study the staff ability to apply information technology at work and analyze the elements to confirm their skills in educational institutions in the 4 southern border provinces of Thailand. This study employed a sequential exploratory mixed methods research design under a pragmatist paradigm. A qualitative approach was conducted first, then the results obtained were used for the quantitative phase. In the qualitative phase, an interpretive phenomenological approach was employed with the data collected from key participants who were selected using purposive and convenience sampling techniques. They are homogeneous and saturation was reached at 7 individuals. The qualitative data were collected through in-depth interviews and analyzed thematically. Quantitative data were collected using a questionnaire with an overall reliability coefficient of .95 from 400 participants who were selected using simple random sampling. Statistical software, including the calculation of mean, standard deviation, confirmatory factor analysis, and structural equation modeling, was employed to assess if the model fits the empirical data. Findings revealed that the skills of personnel capable of utilizing information technology for work in educational institutions include the ability to connect devices to the internet, the use of information technology and digital devices, learning to develop the use of information technology and digital technology, and communication using information technology and digital technology. The confirmatory factor analysis of personnel skills was consistent with empirical data, with an index of goodness-of-fit (χ2) of 12.26, df=10, p=0.268, GFI=0.992, AGFI=0.973, and RMR=0.015. This indicates that the personnel skill model can be used to explain the use of information technology for work in educational institutions and is consistent with the empirical data.